Occupational choice and social contacts across regions - Stefan Bauernschuster; Oliver Falck; Stephan Heblich (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2008)
This paper tests the importance of social contacts on entrepreneurship. To measure differences in the interconnectedness of social contacts, we compare rural and agglomerated areas. A smaller community size in rural areas generates greater network closure. Agents' neighborhoods are more likely to overlap, which intensifies social contacts and thus facilitates resource mobilization. Analyzing the impact of social contacts across regions, we find that greater network closure increases the likelihood of being an entrepreneur by 1.9 to 14.2 percentage points, depending on the number of underlying social contacts. These results remain robust after applying matching techniques and concentrating on young entrepreneurs.
Keywords: J24; Z13; 330; Occupational choice; entrepreneurship; social contacts; Berufswahl; Unternehmer; Selbstständige; Soziale Beziehungen; Soziales Netzwerk; Stadtgröße; Deutschland